Identifikasi Kandungan Metampiron dalam Obat Tradisional Sediaan Jamu Pegal Linu di Wilayah Kecamatan Buleleng, Kabupaten Buleleng - I Made Wisnu Brama Wardana (Universitas Pendidikan Ganesha, 2021)
This research is a descriptive study that aims to determine the presence of methampyrone in traditional herbal medicine for stiff rheumatic preparations in the Buleleng District, Buleleng Regency. The subject of this study was herbal medicine in solid dosage form in powder form, which was suspected to contain methampyrone, and the object of this study was methampyrone, which was suspected to be present in the herbal medicine. The identification of methampyrone was carried out by the method of changing color and the presence of sulfur dioxide gas. The results showed that out of ten samples of aching rheumatic herbal medicine, one sample was positive for methampyrone, as evidenced by a change in color and the presence of sulfur dioxide gas in the herbal sample.